Data integration using service composition in data service middleware. Issue 11 (10th December 2013) - Gannouni, Sofien; Beraka, Mutaz; Mathkour, Hassan
ABSTRACT Service‐oriented computing has emerged as the state‐of‐the‐art distributed computing model for loosely coupled service‐centric business applications. Specifically, service‐oriented computing techniques allow organizations to compose Web services. Indeed, the organizational capacity to compose Web services has received much interest, particularly with respect to supporting business‐to‐business or enterprise application integration. In this paper, we present a system that proposes to adopt service composition as a new approach to integrate data from various data sources. We specify the business process description language as well as the service composition engine that supports the proposed language. We also present different strategies for executing a composite data service call. Copyright © 2013 John Wiley & Sons, Ltd.